DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA IN THE CULTURE OF BANTEN PROVINCE - Elen Maulina; Ana Nurhasanah; Zerri Rahman Hakim (Jurnal Pendidikan Dasar, 2024)
This research aims to develop and analyze pop-up book learning media on the cultural charm of Banten province, as well as to determine student responses in using pop-up book media in learning activities in class IV at SDN Banjarsari 2 Serang, which is carried out from May 2023 to by December 2023. This research uses the 4D method with the stages of defining, designing, developing and disseminating, and uses a research sample of 20 class IV students at SDN Banjarsari 2, Serang City. . This pop up book learning media on the cultural charm of Banten province received an average expert assessment of 84.3% in the "Very Suitable" category, and an average student response assessment of 91.8% in the "Very Good" category. . Based on the results of this assessment, it can be said that the pop up book media material on the cultural charm of Banten province is very suitable for use as learning media in class IV elementary schools.